(untitled) (Medicine Today, 2020)
Introduction: Pancytopenia is a common hematological problem with an extensive differential diagnosis and is a challenging problem to the treating physician. Bone marrow aspiration and biopsy is an important diagnostic test for patient management. The objective of this study is to find out the incidence various causes of pancytopenia in patients attending to the Enam medical college hospital in savar. Materials and Methods: This prospective observational study was done in the department of haematology, Enam Medical College Hospital (EMCH) from July 2012 to June 2019. Results: In our study out of 66 patients, 36 (54.55%) were male, 30 (45.45%) were female and male to female ratio were 1.2:1.Generalized weakness 47 (71.21%) and fever 23 (34.85%) were the most common presenting symptoms followed by bleeding 17 (25.76%), weight loss 6 (12.12%), bodyache 6 (9.09%). Most common clinical findings were anemia 57 (86.36%) and bone tenderness 22 (33.33%). Other physical findings were purpura/brusing 13 (19.70%), splenomegaly 10 (15.15%), lymphadenopathy 4 (6.06%) and hepatomegaly 3 (4.55%). Hematological malignancy 29 (43.94%) and hypoplastic marrow 26 (39.39%) were the most common bone marrow finding of pancytopenic patients followed by megaloblastic anaemia 4 (6.06%), leishmaniasias 5 (7.58), and erythroid hyperplasia 2 (3.03%). Acute myeloid leukaemia was the common haematological malignancy 16 (24.24%), others were acute lymphoblastic leukaemia 5 (7.58%). Myelodysplastic syndrome 3 (4.55%), multiple myeloma 4 (6.06%), chronic myelogenous leukaemia in blastic crisis 1 (1.52%). Conclusion: So we concluded that complete workup is essential for all cases of pancytopenia to find out the treatable cases and to reduce the motality and morbidity in serious diseases. Medicine Today 2020 Vol.32(1): 58-61